Evolutionary Dynamics of Human Rotaviruses: Balancing Reassortment with Preferred Genome Constellations - McDonald, Sarah M.; Matthijnssens, Jelle; McAllen, John K.; Hine, Erin; Overton, Larry; Wang, Shiliang; Lemey, Philippe; Zeller, Mark; Van Ranst, Marc; Spiro, David J.; Patton, John T. (PLoS pathogens, 2009)
Group A human rotaviruses (RVs) are a major cause of severe gastroenteritis in infants and young children. Yet, aside from the genes encoding serotype antigens (VP7; G-type and VP4; P-type), little is known about the genetic make-up of emerging and endemic human RV strains. To gain insight into the diversity and evolution of RVs circulating at a single location over a period of time, we sequenced the eleven-segmented, double-stranded RNA genomes of fifty-one G3P[8] strains collected from 1974 to 1991 at Children's Hospital National Medical Center, Washington, D. C. During this period, G1P[8] strains typically dominated, comprising on average 56% of RV infections each year in hospitalized children. A notable exception was in the 1976 and 1991 winter seasons when the incidence of G1P[8] infections decreased dramatically, a trend that correlated with a significant increase in G3P[8] infections. Our sequence analysis indicates that the 1976 season was characterized by the presence of several genetically distinct, co-circulating clades of G3P[8] viruses, which contained minor but significant differences in their encoded proteins. These 1976 lineages did not readily exchange gene segments with each other, but instead remained stable over the course of the season. In contrast, the 1991 season contained a single major clade, whose genome constellation was similar to one of the 1976 clades. The 1991 clade may have gained a fitness advantage after reassorting with as of yet unidentified RV strain(s). This study reveals for the first time that genetically distinct RV clades of the same G/P-type can co-circulate and cause disease. The findings from this study also suggest that, although gene segment exchange occurs, most reassortant strains are replaced over time by lineages with preferred genome constellations. Elucidation of the selective pressures that favor maintenance of RVs with certain sets of genes may be necessary to anticipate future vaccine needs.